“Each of Our Springs Has Lost Its Miraculous Power”: The Range of a Religious Hotspot – A Distant Reading of Lourdes Representations in Denmark 1858–1914 - Baunvig, Katrine Frøkjær (Numen, 2023)
This article seeks to apply Marianne Qvortrup Fibiger’s theoretical concept of a “religious hotspot” to the case of representations of the French Catholic shrine of Lourdes in Danish (Protestant or post-Protestant) public media from 1858 to 1914. While suggesting that hotspots could be seen as centers in wider interest spheres, I seek to demonstrate the push and pull effects of the hotspot of Lourdes, moving from the local level of the Pyrenees to the national level of France and, further, to the broader Catholic and freethinking-intellectual worlds before I finally arrive at relatively distant Denmark. Here, the development of the representations of Lourdes from 1858 to 1914 mirrors public representations of “the fantastic” and of religiosity as such in the late nineteenth and early twentieth centuries. Beginning with disdain, the Lourdes representations end in nostalgic fascination – in a longing for the enchanted hotspot no longer available (that is, no longer deemed plausible) in Denmark at the opening of the twentieth century. Further, this case helps evaluate the dynamics of exoticism that I propose to be an integral part of religious hotspots per se; in addition, it helps tweak out the commercial nature intrinsic to religious hotspots.